Partial Hydatidiform Mole With Extensive Angiomatoid Vessel Configuration in a First Trimester Miscarriage. (May 2015) - Feist, Henning; Caliebe, Almuth; Oates, Jennifer; Sarioglu, Nanette; Hussein, Kais
Abstract : We report a first trimester miscarriage (9 wk gestation) with a macroscopic grape-like aspect due to extensive angiomatoid changes with widened communicating thin-walled villous vessels. Fluorescence in situ hybridization analysis and microsatellite analysis revealed a diandric triploidy of the trophoblastic tissue, so this miscarriage is indeed a genetic partial hydatidiform mole. This is remarkable since the typical morphologic hallmarks of partial hydatidiform mole, especially enhanced trophoblastic proliferation and marked villous cistern formation, were not prominent. The finding of extensive angiomatoid morphology is to our knowledge an undescribed morphology of an early partial hydatidiform mole. It serves as an example of the morphologic variability of this probably underestimated condition that has a slightly elevated risk for the development of gestational trophoblastic disease.